How COVID-19 has changed the utilization of different health care services in Poland - Magdalena Mrożek-Gąsiorowska; Marzena Tambor (BMC, 2024)
Abstract Background The COVID-19 pandemic has affected health care systems in many ways, including access to and the use of non-COVID services. The aim of the study was to assess the impact of the pandemic on the utilization of different public health care services in Poland. Methods The aggregated data on health care users and provided services for the years 2015/2016-2021 were used to analyse the changes in health care utilization during the pandemic and deviations from pre-pandemic utilization trends. Quantitative analysis was complemented with qualitative descriptions of the changes in principles of health care provision during the pandemic. Results The results show a considerable drop in the provision of most health care services in 2020 that in some cases disturbed pre-pandemic utilization trends and was not made up for in 2021. The most significant decrease has been observed in the field of preventive and public health services, as well as rehabilitation. The provision of these services was put on hold during the pandemic. Conclusions The accumulated COVID-19-related "health debt" urgently calls for government actions to strengthen disease prevention and health promotion in Poland.